2014
DOI: 10.1021/am502359k
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Nonlinear Phonon Shifts in a Supported MoS2 Monolayer

Abstract: We report Raman spectra measurements on a MoS2 monolayer supported on SiO2 as a function of temperature. Unlike in previous studies, the positions of the two main Raman modes, 2 1 and 1 exhibited nonlinear temperature dependence. Temperature dependence of phonon shifts and widths is explained by optical phonon decay process into two acoustic phonons. Based on Raman measurements local temperature change under laser heating power at different global temperatures is derived. Obtained results contribute to our und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
82
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 29 publications
17
82
1
Order By: Relevance
“…In this respect, resonant Raman spectroscopy with varying photon energies provides a complementary tool to emission and absorption measurements to access the electronic structure in SCTMDs as well as to study fundamental aspects of the electron-phonon interaction [134,136,137] . Already nonresonant Raman spectroscopy, meaning that neither the exciting (incoming resonance) nor the scattered photon energy (outgoing resonance) meet an optically active interband transition of the electronic bands, provides access to the number of layers [81,[138][139][140][141][142] , phase transition 2H, 3R, 1T, 1T' MX2 crystals [137,143,144] , strain [69,145,146] , disorder and defects [147] , doping [74,148] and temperature as well as thermal conductivity [97,[149][150][151][152] . Amazingly, this information can already be extracted by investigating only two Raman active zone center phonon modes in the higher frequency range (ωph > 200 cm -1 ).…”
Section: First Order Phonon Modes As Unique Fingerprint For Materials mentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, resonant Raman spectroscopy with varying photon energies provides a complementary tool to emission and absorption measurements to access the electronic structure in SCTMDs as well as to study fundamental aspects of the electron-phonon interaction [134,136,137] . Already nonresonant Raman spectroscopy, meaning that neither the exciting (incoming resonance) nor the scattered photon energy (outgoing resonance) meet an optically active interband transition of the electronic bands, provides access to the number of layers [81,[138][139][140][141][142] , phase transition 2H, 3R, 1T, 1T' MX2 crystals [137,143,144] , strain [69,145,146] , disorder and defects [147] , doping [74,148] and temperature as well as thermal conductivity [97,[149][150][151][152] . Amazingly, this information can already be extracted by investigating only two Raman active zone center phonon modes in the higher frequency range (ωph > 200 cm -1 ).…”
Section: First Order Phonon Modes As Unique Fingerprint For Materials mentioning
confidence: 99%
“…Raman measurements with a high spatial resolution can not only be utilized to measure the local temperature but also to investigate the thermal conductivity of a material. It has been shown that both optical phonon modes with E'/E 1 2g and A'1/A1g symmetry of SC-TMDs are lowered with increasing temperature [149][150][151][152] . The first order temperature coefficients T for MoS2 are reported to be linear for both phonon modes.…”
Section: Temperature Shift Of the Phonon Modesmentioning
confidence: 99%
“…The Raman modes of monolayer MoS 2 affected by temperature have been investigated in the literature: Both ‫ܧ‬ ଶ ଵ and ‫ܣ‬ ଵ peaks red-shift when temperature increases. [42][43][44][45][46] From the red-shifts of the both peaks in our samples, the temperature of Ag/Ti covered monolayer MoS 2 increased significantly during the Raman measurement. This heating effect was also observed in the Raman spectrum of few-layer MoS 2 : the two peaks also red-shift simultaneously after Au/Ti film deposition ( Figure 5(d)).…”
Section: Raman Spectroscopy Of Mos 2 Covered With Metalmentioning
confidence: 99%
“…In nanoelectronic device application, it is very important to understand the effect of phonons because the self-heating of the device can significantly affect the performance. The temperature dependence of Raman shift of monolayer and few layer MoS 2 has been extensively studied over a heating process1314, a cooling process15, and a wide temperature range from 77 K to 623 K16. Thermal conductivity of MoS 2 was given out based the temperature dependence of Raman shifts1617.…”
mentioning
confidence: 99%